Collaborative Environmental Governance Frameworks A Practical Guide. - Gieseke, Timothy (Milton : CRC Press LLC, 2019)
This book takes a practical approach to understanding and describing collaborative governance for resolving environmental problems. It introduces a new collaborative governance assessment model and recognizes that collaborations are a natural result of organizations converging around complex issues. Rather than identifying actors by their type of organization, the actors are identified by the type of role they play. This approach is aligned with how individuals and organizations interact in practice, and their dependance on collaborations to solve emerging environmental problems. The book discusses real cases with governance issues and creates new frameworks for collaborations. Features: Addresses communities at all levels and scales that are gravitating toward collaborations to solve their environmental issues. Prepares and enables individuals to participate in collaborative governance and design collaborative governance frameworks. Introduces the first simplified and standardized model to assess governance using governance actors and styles. Explains governance in simple terms and builds governance frameworks from the individual's perspective; the smallest, viable unit of governance in a collaboration. Describes "tools of convergence" for collaborative leaders to organize and align activities to create shared-governance outcomes and outputs.
4.4.11 Information Technology4.4.12 Structure; 4.4.13 Collaborative Clustering; 4.4.14 Governance; 4.5 Governance as a Cornerstone of Collaboration; 4.5.1 Collaborative Frameworks; 4.5.1.1 "Black Box" of Collaboration Processes; 4.5.1.2 Collective Impact Initiatives; 4.5.1.3 Integrated Framework for Collaborative Governance; 4.5.2 Grappling with Collaborative Governance; 4.5.2.1 What is Collaborative Governance?; 4.5.2.2 Managing a Disarticulated State; 4.5.2.3 Sweet Reward?; 4.5.2.4 Identifying the First Steps; 4.5.3 The Collaborative Endgame: Achieving Shared Governance
Description based upon print version of record.
Section II: The Science of Collaborative Governance
OCLC-licensed vendor bibliographic record.
Keywords: Environmental policy; Environmental protection; LAW / Environmental; NATURE / Environmental Conservation & Protection; POLITICAL SCIENCE / Public Policy / General